Translating instructive texts - Vandepitte, Sonia (HERMES - Journal of Language and Communication in Business, 2008)
Starting with Werlich (1982), many researchers within text linguistics and document design see instructive texts as a category that is different from persuasive texts. Others do not include either in their main typologies (e.g. Bonnet et al. 2001). This paper will claim, however, that instructions are a particular subtype of persuasive texts: instructing people is also persuading them to do something in a particular way or in a particular situation or in a particular order. Consequently, all features characteristic of persuasion (e.g. Aristotle 4th c. BC, Bettinghaus 1968, Dacheux 1994, Whalen 1996) also appear in instructive texts. Drawing from a learner corpus of materials used in the Trans-Atlantic Tech Writing / Translation Project (Maylath et al., 2005, in press), in which Flemish students translate English instructive texts written by American students into Dutch, the paper will discuss the problems involved in the translation of two relevant persuasive characteristics of instructive texts: expertise and positive audience-orientation. For the former, attention will be paid to message form, structure and strategy, while the latter will lead to considerations of both individual interpretation differences and cultural differences.